Density Functional Theory Calculations - Ricardo De Lazaro, Sergio; Henrique Da Silveira Lacerda, Luis; Augusto Pontes Ribeiro, Renan (IntechOpen, 2021)
This book is a contribution to the fast and broad Density Functional Theory (DFT) applications of the last few years. Since 2000, the DFT has grown exponentially in several computational areas because of its versatility and reliability to calculate energy from electronic density. The fast DFT's calculations show how scientists develop more codes focused to simulate molecular and material properties reaching better conclusions than with previous theories. More powerful computers and lower computational costs have certainly assisted the increased growth of interest in this theory. Each chapter presents a specific subject contributing to a vision of the great potential of the quantum/DFT simulations in high pressure, chemical reactivity, ionic liquid, chemoinformatic, molecular docking, and non-equilibrium state.